THE APPROACHES TO PROVISION OF INFORMATIONAL SUPPORT TO PARENTS OF CHILDREN WITH VISUAL IMPAIRMENT (Education in the 21st Century, 2023)
In the article, the main approaches and issues to provide informational support to parents of children with visual impairments are disclosed. It is known that the upbringing, education and development of a child start in the family. And the success of the whole correctional- development work depends on the awareness of parents on age related and psychological specifications of children with visual impairments, on the means, methods and conditions of their application for many educational problems. This defines the importance of the comprehensive study of the given issue, elaboration of approaches to provision of informational support to parents in upbringing, education and development of children with visual impairments. The importance of this issue is also defined by the specification of upbringing, education and development of children who have low vision and are blind and the feasibility to implement educational and correctional-development work with these children in family settings.The most prioritized directions of work with the family of a child with visual impairment is outlined in this article, the main questions are mentioned on which regard parents should be informed during organization and implementation of the educational, correctional-developmental and other types of works with the child in the settings of a family.